Osnovne značilnosti vetrov za jadralce in kajtarje v Sloveniji in bližnji okolici - Polajnar, Janez (Šport (Ljubljana), 2018)
The purpose of this paper is to present natural phenomena that enable the development of the appropriate wind speed in the territory of Slovenia and its surrounding area, for the purpose of sport recreational activities on the water. In the article we describe the characteristics of the most frequent winds in the Adriatic Sea, which are suitable for windsurfing and kitesurfing, as well as for all other sports that are powered by wind speed. We also described the basic principles for the formation of the winds. The contribution is useful for all those who are interested in the formation of the winds in Slovenia and its surrounding area.
Keywords: jadranje na deski; kajtanje; meteorološki modeli; Slovenija; vetrovi (meteorologija); vodni športi